Reading the Locust Plague in the Prophecy of Joel in the Context of African Biblical Hermeneutics and the Decolonial Turn - Udoekpo, Michael Ufok (Religions, 2023)
Joel is one of the 12 minor prophets (dōdekaprophēton). His prophecy aims at calling the nation and people to repentance through emphasizing that the Day of the Lord (yōm ădȏnay) is at hand (3:1–5 [2:28–32]). The locust plague (ʾarbbeh) in Joel’s message—which recalls the insects that threaten to destroy crops and vegetation in Africa and beyond, but which can also be used as food and livestock feed and offer other benefits as well—could be interpreted as Joel’s prophetic sign that the great Day of the Lord is near (1:2–2:17). Throughout history, scholars, theologians, and exegetes of differing schools of thought and from numerous locations have offered various interpretations for Joel’s prophecy and subjected it to diverse Eurocentric and Americo-centric hermeneutical methods. This work, however, with its focus on Africa, takes a different approach. Drawing from the work of many African hermeneuticians, it reads Joel’s prophecy using the tools of African Biblical Hermeneutics (ABH), a post-colonial enterprise, in light of the decolonial turn. The article exegetes and theologically analyzes the narrative of the locust plague (ʾarbbeh) in Joel 1:2–7, within the context of Joel 1–3, with the hopes that it will be transformational and beneficial for African readers within their faith context.